Kegiatan Sosialisasi Keselamatan Dan Kesehatan Kerja Pada Tambang Batu Gamping di PT. Diamond Alfa Propertindo Kabupaten Buton Tengah - Aldiyansyah, Aldiyansyah; Siharis, Al Amin; Abriansyah, Abriansyah; Amin, Fitrani; Ramadhan, Aqsal (Anoa : Jurnal Pengabdian Masyarakat Fakultas Teknik, 2023)
PT. Diamond Alfa Propertindo is a company that produces gravel stones ranging from 0.5 cm to 3 cm in size, located in Southeast Sulawesi, with a land area of 4,905 hectares. PT. Diamond Alfa Propertindo has a production target of 25,000 tons per month, with an average production of 22,000 tons per month. The company employs open-pit mining using the Quarry method, with mining locations divided into blocks A1, A2, A3, currently in the mining phase. The extraction of limestone involves drilling and blasting activities to meet production targets, posing high risks of workplace accidents, occupational diseases, fires, explosions, landslides, and environmental pollution. These risks arise from workers' non-compliance with safety regulations, unsafe working conditions, inadequate facilities and infrastructure, or poor management, as well as unsafe environmental conditions. The implementation of Occupational Health and Safety (K3) is the responsibility of every mining employee, from the highest leadership level to field executives or operators. This is conveyed through a combination of methods such as lectures, discussions, and demonstrations. The community service activities aim to ensure that the limestone mining activities of PT. Diamond Alfa Propertindo in Buton Tengah are carried out with an understanding of the importance of occupational health and safety in creating a comfortable and safe working environment for mining workers.